Association of blood pressure with mortality in hemodialysis patients with a tunneled cuffed catheter: A single-center observational study. Issue 37 (11th September 2020) - Shimamura, Yoshinosuke; Maeda, Takuto; Abe, Koki; Takizawa, Hideki
Abstract : Abstract: The use of tunneled cuffed catheters (TCCs) for permanent blood access is increasing as the hemodialysis population ages. However, the higher mortality and complication rates associated with their use have been significant concerns. This single-center observational cohort study aimed to investigate clinical factors affecting mortality and complications in Japanese hemodialysis patients with a TCC. We enrolled 64 consecutive patients receiving hemodialysis through a TCC between 2012 and 2019. The primary outcome was all-cause mortality and the secondary outcome was the incidence of catheter-related complications at 2 years. Cox proportional hazards models were used to examine variables associated with these outcomes. At 2 years, death from any cause and catheter-related complications occurred in 27/64 (42%) and 23/64 (36%) patients, respectively. There were 14 bacteremia events, 7 catheter obstructions, and 8 instances of restricted blood flow. Multivariate analysis showed that systolic blood pressure (SBP) < 100 mm Hg at the time of catheter insertion was associated with higher all-cause mortality (hazard ratio, 2.59; 95% confidence interval, 1.05–6.41) and catheter-related complications (hazard ratio, 2.57; 95% confidence interval, 1.52–22.2). The Kaplan–Meier analyses also showed that patients with SBP <100 mm Hg had higher mortality ( P  = .001) and a higher incidence of catheter-related complications ( P  = .0068). SBP <100 mm Hg at the time of catheter insertion is associated with mortality and catheter-related complications in hemodialysis patients using a TCC. Further multi-center studies are required to validate our results.